Impact of climate induced hypoxia on calcifying biota in the Arabian Sea : An evaluation from the micropaleontological records of the Indian margin - SINGH, A.D.; DAS, S.; VERMA, K. (MAUSAM, 2011)
High biological productivity combined with the poor ventilation produces severe oxygen depletion (hypoxia) in upper intermediate waters of the Arabian Sea. The naturally developed Arabian Sea oxygen minimum zone (OMZ) is one of the most pronounced low oxygen ocean environments known today. The OMZ impinges the Indian margin where oxygen concentration reaches values less than 0.05 ml/l leading denitrification. In recent studies, it has been observed that the OMZ strength has varied considerably in the past, in tune with the global climate change. But the effect of changes in natural mid-water hypoxic environment on the marine biota particularly of the eastern Arabian Sea is unknown. Here, we analyzed 30,000 yr record of temporal changes in two major groups of marine calcifying microfauna pteropods secreting aragonitic shells and foraminifera secreting calcitic shells in terms of abundance and diversity variations. This study will provide an insight into our understanding of potential impact of rising atmospheric CO2 on marine ecosystem.